Character Education in the Shadow of Global Competition - St. Rahmah; Taufiqurrahman; Ahmad Syafie; Maryam Ilyasovna; Noorhani Dyani Laksmi (Mahkota Science Publishers, 2026)
Character education in Indonesia faces an existential paradox, as the moral values that should liberate people are at risk of being reduced to tools of adaptation within a market logic that demands relentless efficiency, productivity and competitiveness. This study aims to develop a conceptual framework to explain the relationship between local character values and global competencies, and to explore how integrating the two can be implemented in educational practice. This study employs a sequential explanatory design, enabling both in-depth exploration and testing of conceptual relationships. The findings confirm that character education in Indonesia faces not merely implementation challenges, but is caught in a deeper epistemological crisis, wherein moral values are produced, negotiated, and even compromised within the framework of a non-neutral global competitive rationality, thus revealing that the education system implicitly has the potential to act as an agent reconstructing morality according to market logic, rather than merely transmitting noble values. The contribution of this study lies in dismantling the assumption that character education is inherently noble, by demonstrating that without structural transformation, it may instead function as symbolic legitimisation for contradictory educational practices, whilst simultaneously offering a new conceptual direction that positions character as a critical arena between resistance and adaptation.